Association of complement C3 gene variants with renal transplant outcome of deceased cardiac dead donor kidneys - Damman, J; Leuvenink, H; Ploeg, R; Daha, MR; Born, J; De Borst, M; Bakker, S; Navis, G; Seelen, M; Van Goor, H; Hillebrands, J; Dijk, M; et al. (2012)
Local renal complement activation by the donor kidney plays an important role in the pathogenesis of renal injury inherent to kidney transplantation. Contradictory results were reported about the protective effects of the donor C3F allotype on renal allograft outcome. We investigated the influence of the donor C3F allotype on renal transplant outcome, taking all different donor types into account. C3 allotypes of 1265 donor-recipient pairs were determined and divided into four genotypic groups according to the C3F allotype of the donor and the recipient. The four genotypic groups were analyzed for association with primary nonfunction (PNF), delayed graft function, acute rejection, death-censored graft survival and patient survival. Considering all donor types, multivariable analysis found no association of the donor C3F allotype with renal allograft outcome. Also, for living and deceased brain-dead donors, no association with allograft outcome was found. Post hoc subgroup analysis within deceased cardiac dead (DCD) donors revealed an independent protective association of donor C3F allotype with PNF. This study shows that the donor C3F allotype is not associated with renal allograft outcome after kidney transplantation. Subgroup analysis within DCD donors revealed an independent protective association of the donor C3F allotype with PNF, which is preliminary and warrants further validation. The donor complement C3F allotype is not associated with renal allograft outcome after kidney transplantation; however, post-hoc analyses within donation after cardiac death donors suggests its protective association with primary nonfunction. © copyright 2011 The American Society of Transplantation and the American Society of Transplant Surgeons.